HUBUNGAN TINGKAT STRESS DENGAN KUALITAS TIDUR PADA MAHASISWA TINGKAT AKHIR UNIVERSITAS BHAKTI KENCANA - anri (Jurnal Ilmiah Cerebral Medika, 2021)
Introduction: Higher education is a level of education after junior high school which includes D III, S-1, S-2, specialist and S-3 education programs organized by universities. Academic life that can cause stress for students, namely changes in learning styles from high school to higher education, lecture assignments, target value achievement, academic achievement, and the need to organize yourself and develop better thinking skills. Especially stress on final semester students, namely to make a final scientific paper or thesis. Methods: The type of research used is descriptive correlation which is looking for a relationship between the two or more phenomena, and uses a cross sectional approach with a sample of 100 people with stratified random sampling technique. The data collection method uses primary data by distributing questionnaires that are distributed and filled in by students who are working on scientific papers at Bhakti Kencana University Prodi D III Nursing. The questionnaire used uses a standardized questionnaire that is adopted from the Safira and Safutra questionnaires (2009) regarding stress levels. The questionnaire was modified by researchers using language that is easy to understand, clearly in accordance with the sample situation, namely final year students working on scientific papers. Results: The results of the analysis of the relationship between stress levels and sleep quality disorders obtained a p-value (0.004) <alpha value (0.05) so that H0 was rejected. Hı was accepted. Conclusion: there is a significant relationship between stress levels and sleep quality disturbances in D III students currently doing KTI.